Spikes blocking and surge protection - Torla, Ahmad Lutfi; Khan, Sheroz; Abdul Muthalif, Asan Gani (IIUM Press, 2011)

(untitled)
In order to ensure a constant voltage source, we employ line regulation, load regulation and ripple rejection. These are often small deviations in the input voltage. A spike or surge is a sudden large deviation in the circuit that usually only lasts for a very short period of time, for example lightning surges. This characteristic means that regulator circuits designed for line regulation and ripple rejection may not be able to handle the large load of a surge and may not be able to respond fast enough to make any meaningful difference [1]. Spikes are extremely damaging to a circuit since the voltage of a spike such as a lightning surge can be thousands of times the intended voltage of the circuit